Mastalgia: a serious problem of women at premenopausal age - Pertyński, Tomasz; Stachowiak, Grzegorz (Menopause Review/Przegląd Menopauzalny, 2013)
Mastalgia is a frequent premenopausal symptom. Given the influence of the menstrual cycle, cyclical and non-cyclical mastalgia are typically distinguished. This article describes hormonal changes occurring during the premenopausal period and their influence on breast pains. The authors underline that prior to the onset of pharmacological treatment, any breast cancer lesions should be excluded. The treatment of mastalgia includes also female life-style changes as well as some psychoprophylactic actions. Special attention was paid to progestogens, including their potential relation to the breast cancer risk. Administration of MHT in mastalgia women remains an unsolved issue; a decision to start (or continue) this therapy should be each time made on a case-by-case basis, following the patient’s consultation.